Associations between exercise capacity, p16INK4a expression and inflammation among adult survivors of childhood cancer - Goodenough, Chelsea G.; Wogksch, Matthew D.; Kundu, Mondira; Lear, Matthew; Thomas, Paul G.; Srivastava, Deo Kumar; Wang, Zhaoming; Armstrong, Gregory T.; Hudson, Melissa M.; Robison, Leslie L.; Ness, Kirsten K. (Frontiers in Oncology, 2022)
Background: Over 50% of childhood cancer survivors are exercise intolerant, with maximal aerobic capacities comparable to individuals decades older, suggesting early physiologic ageing. In addition, 36% of survivors are obese. Optimal exercise capacity provides a foundation to support daily function and healthy body habitus and is associated with benefits to cognition, cardiovascular health, and longevity. Cellular senescence and inflammation are key mechanisms that drive age-related disease, quantifiable as biomarkers in peripheral blood. Aims: This study aimed to evaluate associations between p16INKa, a biomarker of cellular senescence, and inflammation and exercise capacity among adult survivors of childhood cancer. Materials and Methods: Eligible survivors were recruited from the St. Jude Lifetime (SJLIFE) Cohort Study. Exercise capacity was assessed by maximal oxygen uptake (VO2, ml/kg/min) obtained via cardiopulmonary exercise testing using a modified Bruce protocol. Body fat (%) was determined from dual energy x-ray absorptiometry (DEXA). Peripheral blood samples were used to evaluate log2 p16INK4a mRNA expression, a biomarker of cellular senescence, and inflammation with high sensitivity C-reactive protein (hs-CRP) levels. Multivariable regression evaluated associations between p16INK4a, hs-CRP, body fat, and exercise capacity. Results: Participants included 185 five-year childhood cancer survivors (mean age 36.6 [range 20.1 - 55.7] years, 44% male, 77% non-Hispanic white, 53% leukemia/lymphoma). Compared to males, females had lower peak VO2 (mean+SD, 23.7+7.8 vs. 31.8+7.1 ml/kg/min, p=0.01), higher p16INK4a expression (9.6+1.2 vs. 9.2+1.2 fold, p=0.02), and hs-CRP concentration (5.9+8.4 vs. 3.3+3.9 mg/L, p=0.01). Among females (n=103), hs-CRP concentration (β -0.2, 95% CI -0.34 to -0.05, p=0.01) and p16INK4a expression (β-5.32, 95% CI 10.42 to -0.22, p=0.04) were inversely associated and statistically significant with peak exercise capacity, with a significant interaction between p16INK4a expression and body fat (β 0.15, 95% CI 0.02 to 0.28, p=0.03). Among males (n=82), p16INK4a expression (β -1.01, 95% CI -2.14 to 0.12, p=0.08), and body fat (β -0.54, 95% CI -0.70 to -0.38, p<0.01) were inversely associated with peak exercise capacity. Conclusion: Inflammation and p16INK4a expression are associated with lower exercise capacity in childhood cancer survivors, suggesting potential targets or outcome measures for interventions designed to prevent or remediate accelerated physiologic ageing in this population.